2016
DOI: 10.3855/jidc.7049
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis spp lactis infection in infants with chronic diarrhea: two cases report and literature review in children

Abstract: Lactococcus lactis is a gram-positive, facultative anaerobic coccus that is occasionally isolated from human mucocutaneous surfaces such as the intestines. It is used in the dairy industry for milk acidification and is mostly nonpathogenic in immunocompetent humans, however a number of cases of infection with L. lactis have been reported in recent years. In this article, we describe two cases of infection due to L. lactis in patients with chronic diarrhea. The first case is a five-month-old boy who was operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…were identified in 15% of the samples. Although lactococci have recently been associated with human disease, [51][52][53] we concluded that, based on the clinical evaluation, the lactococcal DNA was most likely a contaminant introduced at the time of tympanocentesis.…”
Section: Discussionmentioning
confidence: 91%
“…were identified in 15% of the samples. Although lactococci have recently been associated with human disease, [51][52][53] we concluded that, based on the clinical evaluation, the lactococcal DNA was most likely a contaminant introduced at the time of tympanocentesis.…”
Section: Discussionmentioning
confidence: 91%
“…We previously reported that K17+ filaments were found to be distributed in a limited area in ring- or net-like shapes in the HaCaT cell line, which are immortalized keratinocytes, following exposure to nisin, a product of Lactococcus lactis subsp. lactis 22 , one of the resident members of bacterial flora on the oral mucosa 35 . Such abnormal cytoskeletal arrangement may also be considered to be due to keratinocyte damage or activation 22 , though the stimulating factors in cases of oral lichen planus are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although Lactococcus lactis is primarily known to be non-pathogenic, the pathogenicity of this agent should be kept in mind. Indeed, recent cases of Lactococcus lactis infections have been reported [10,16,26]. One hundred and twenty-five samples were collected from patients, of whom 62 were male (49.6%) ( p = 0.9287).…”
Section: Discussionmentioning
confidence: 99%
“…Deemed harmless to humans, their use is widespread in the food industry. However, rare cases of infections of greater or lesser severity have been reported in humans [10], and although few in number, some studies have reported Lactococcus lactis in endodontic infections [11,12,13]. Koyuncu et al (2005) [14] reported a deep neck infection due to Lactococcus lactis with the consumption of unpasteurized milk, occurring in a patient with a buccal mucosa tumor.…”
Section: Introductionmentioning
confidence: 99%